Southern ladies, new women : race, region, and clubwomen in South Carolina, 1890-1930 - Johnson, Joan Marie (New perspectives on the history of the South., 2004)
Investigates how the desire to create a distinctive southern identity influenced black and white clubwomen at the turn of the 20th century and motivated their participation in efforts at social reform. Often doing similar work for different reasons, both groups emphasized history, memory, and education.